2020
DOI: 10.1111/jocs.14711
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum‐assisted extraction of ilio‐caval and right heart masses: A 5‐year single center experience

Abstract: Purpose Despite paucity of data, there exists growing popularity of catheter‐based extraction methods for intravascular thrombi and vegetations. We describe a large single center experience with vacuum‐assisted extraction techniques (VAET) for right‐sided intravascular and cardiac masses. Methods We retrospectively reviewed the perioperative course of patients undergoing VAET between 2014 and 2019. Primary outcomes were survival and freedom from recurrent bacteremia. Procedural success was a composite definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The indication for the procedure was a right heart mass in 52.6% of cases; intraprocedural success, defined as >70% mass removal, was achieved in nearly 60% of patients with right heart masses [ 13 ]. Our own results coincide with previously published data, as seen in Table 4 , demonstrating good intraoperative success [ 5 , 7 , 14 16 ]. Likewise, these results also support the use of AngioVac as a treatment option for critically ill patients with right-sided heart masses, as seen in Figure 2 .…”
Section: Discussionsupporting
confidence: 92%
“…The indication for the procedure was a right heart mass in 52.6% of cases; intraprocedural success, defined as >70% mass removal, was achieved in nearly 60% of patients with right heart masses [ 13 ]. Our own results coincide with previously published data, as seen in Table 4 , demonstrating good intraoperative success [ 5 , 7 , 14 16 ]. Likewise, these results also support the use of AngioVac as a treatment option for critically ill patients with right-sided heart masses, as seen in Figure 2 .…”
Section: Discussionsupporting
confidence: 92%
“…Excluding duplicates, 41 case reports and 37 irrelevant studies, 11 studies were included in this targeted literature review. [16][17][18][19][20][21][22][23][24][25][26] Among these, 2 were abstracts and 9 were manuscripts.…”
Section: Resultsmentioning
confidence: 99%
“…However, two studies with more severe patients reported patients with a worsening degree of tricuspid regurgitation, though it was unclear the degree to which the worsening severity was due to the debulking procedure. 21,24 Furthermore, a recent study analyzing data from the registry to assess safety and procedural outcomes of using the AngioVac at University of California, Los Angeles did not report any valve damage. 28 In all, more data are needed in evaluating the impact of such procedure on tricuspid valve damage as part of the safety profile of the AngioVac system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Case-reports describe safe right heart thrombi extraction. [7][8][9][10][11] Although no anatomical, age, or weight restrictions exist, AVS has been rarely used in Fontan physiology. 12,13 One case report describes the use of AVS concurrent with veno-arterial-ECMO (VA-ECMO) in a previously healthy, 72 kg 12-year-old with cannula-tip thrombus.…”
mentioning
confidence: 99%